Case report: Wrist neuropathic arthropathy secondary to syringomyelia [Siringomiyeliye baǧli el-el bileǧi nöropatik artropatisi: Olgu sunumu] - (:unkn) unknown (My University, 2009)
Neuropathic arthropathy is a progressive, degenerative arthritis affecting one or more peripheral or vertebral articulations and is associated with an underlying central or peripheral neurological disorder. Diabetes mellitus and syphilis are among the most common causes of the neuropathic arthropathy. Syringomyelia is a chronic progressive degenerative or developmental disorder of the spinal cord and may lead to neuropathic arthropathy in the upper extremities. Herein, we report a case of neuropathic arthropathy with wrist involvement secondary to syringomyelia. © Turkish Journal of Physical Medicine and Rehabilitation, Published by Galenos Publishing. All rights reserved.
Keywords: Charcot joint; Neuropathic artropathy; Syringomyelia